2021
DOI: 10.1111/jace.18179
|View full text |Cite
|
Sign up to set email alerts
|

Apatite and garnet stability in the Al–Ca–Mg–Si–(Gd/Y/Yb)–O systems and implications for T/EBC: CMAS reactions

Abstract: This work advances the understanding of the influence of rare earth (RE) ion radius on the stability and extent of the garnet solid solution phase in the (ytterbia/yttria/gadolinia)‐calcia‐magnesia‐alumina‐silica systems. Guided by the crystal chemistry and charge neutrality constraints, selected compositions in the notional garnet stability field were synthesized, equilibrated at 1400°C, and characterized to determine the equilibrium phases and their compositions. The results show a significant reduction in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…The solutions were mixed in appropriate proportions and added dropwise to aqueous ammonium hydroxide with pH ≥ 10 maintained during the precipitation. The precipitates were separated by centrifugation, washed with ethanol, dried, pyrolyzed at 1000 • C, ball milled (25 Hz, 4 h, zirconia media), cold pressed into 6 mm diameter pellets, and sintered in air at 1400 or 1500 • C for times totaling between 1 and 250 h. The temperatures were selected based on prospective coating temperatures for turbine engines and knowledge of GdAG metastability around 1400 • C. 15 Four pellets were sintered for the shortest time. Then, one pellet was removed from the set for microstructure characterization and the remaining samples were sintered to achieve the next desired total sintering time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solutions were mixed in appropriate proportions and added dropwise to aqueous ammonium hydroxide with pH ≥ 10 maintained during the precipitation. The precipitates were separated by centrifugation, washed with ethanol, dried, pyrolyzed at 1000 • C, ball milled (25 Hz, 4 h, zirconia media), cold pressed into 6 mm diameter pellets, and sintered in air at 1400 or 1500 • C for times totaling between 1 and 250 h. The temperatures were selected based on prospective coating temperatures for turbine engines and knowledge of GdAG metastability around 1400 • C. 15 Four pellets were sintered for the shortest time. Then, one pellet was removed from the set for microstructure characterization and the remaining samples were sintered to achieve the next desired total sintering time.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the mixed Y + Gd samples capture the transition from the G + F to Al 2 O 3 + P + F equilibrium assemblages. However, experimental studies have shown that while the equilibrium YAG crystalizes directly during synthesis, 14 the equilibrium Al 2 O 3 + GdAP assemblage is slow to develop with metastable GdAG existing for extended time at 1400°C 15 . The Gd‐ and Y‐based fluorite compositions predicted to form at equilibrium in these samples, that is, Y 33 Zr 67 and Gd 35 Zr 65 from the 1500°C sections, were studied for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…The EPMA characterization of the RE = GdY and GdYbY samples used previously reported methods. 39,46 EPMA of samples with RE = GdLaNdYbY used a Cameca SX100/SXFive FE-EPMA with beam energy of 12 keV and Depending on the grain size and distribution, point measurements were made for between four and ten grains of each phase. Average compositions are reported; standard deviations were generally less than 0.3 mol% for each oxide but occasionally as high as 1 mol%, especially for smaller grains.…”
Section: Characterizationmentioning
confidence: 99%
“…The RE 3 Al 5 O 12 stoichiometry crystallizes in the garnet (G) structure with Al filling the B and T sites. This phase is stable for the smaller RE 3+ and is also known for persistent metastability for other stoichiometries 38–40 . Finally, REAl 11 O 18 is an alkali‐earth deficient magnetoplumbite (β‐Al 2 O 3 ) variant formed for the largest RE 41,42 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation